New prospects for ultrasound examination of abdominal organs state in newborn children with gastroschisis - M. I. Pykov; Е. A. Filippova; O. V. Teplyakova; Е. I. Dorofeeva; N. N. Dzhandzhgava (Медицинский совет, 2018)
Gastroschisis is a complex anterior abdominal wall defect requiring urgent surgical repair. Oneor two-stage surgery to return the intestines to the abdominal cavity may result in developing acute renal failure. Preservation of the Arantsiev duct lumen provokes serious changes in the portal vein system. The state of the microcirculatory bloodstream in the intestinal wall clearly correlates with the clinical data indicating the restoration of the passage through the gastrointestinal tract.